Development Of Interactive Wordwall Activity-Based Learning Media For Whole Number Concept In Grade 2 At Balonggemek 1 Public Elementary School - Umul Maulifah; Adi Bandono; Agung Pramujiono; Elis Dwi Purwaningsih (At Turots: Jurnal Pendidikan Islam, 2026)
This research was motivated by the need for interactive and engaging learning media to help second-grade students understand the concept of whole numbers. Mathematics learning in lower grades is often delivered through conventional methods, which can make students easily bored and less motivated. The use of digital tools such as Wordwall is expected to create a more enjoyable, participatory, and student-centered learning atmosphere. The study employed a Research and Development (R&D) method using the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The participants were second-grade students at SD Negeri Balonggemek 1. Data were collected through observation, interviews, questionnaires, and learning outcome tests. Validation by media and material experts was conducted to assess the feasibility of the developed product. The results indicated that the Wordwall-based learning media was highly feasible, with an average validation score above 90%. The practicality test showed that both teachers and students found the media easy to use and engaging, achieving an attractiveness level of 94.3%. In addition, students’ learning outcomes improved significantly after using the media, as seen from the increase in post-test scores compared to pre-test results. In conclusion, the Wordwall learning media for whole numbers material is effective for use in second-grade mathematics learning. It not only improves students’ conceptual understanding but also enhances their enthusiasm and motivation to learn actively.